Upgrading Bahan Bakar Jumputan Padat (BBJP) Sebagai Co firing Sistem Tenaga Uap Melalui Thermal Drying dan Fermentasi - Mastur, Mastur; Sugiantoro, Bambang; Prabowo, Nugrah Rekto; Supiyana, Nana; Sutisna, Utis (P3M Politeknik Negeri Cilacap, 2024)
The waste sorting process produces organic and inorganic waste. It can be converted into Solid Recovered Fuel with the addition of a maximum of 20% plastic, which can be used for co-firing coal combustion in steam power systems. High humidity levels and the condition of organic waste with its various constituent components require drying and other treatments to increase the calorie content. Types of organic waste treatment, methods of drying, and decomposition of organic waste went through a fermentation process. The research aims to identify the effect of fermentation, addition of biomass, and plastic shreds of BBJP products on density, ash content, chlorine, and calorific value. Dimensions of organic waste powder at a level of 50 mesh and plastic shreds of 5-10 mesh are aimed at increasing the pellet/SRF bond. Mechanical testing data in the form of compression testing resulted in a level of resistance that exceeded pellet strength requirements and increased by 67%. Chlorine and sulfur levels are approaching the limit, but ash levels are still high. The calorific value of pellets in the fermented organic waste specimen treatment produces a higher calorific value compared to other treatments. Research on converting waste into co-firing fuel in solid form with the criteria for calorific value and physical properties that comply with the technical requirements for co-firing steam-powered systems can still be optimized to produce fuel with a higher calorie content. Reducing chlorine, sulfur, and ash levels is done for a low-carbon and environmentally friendly combustion process.